2019
DOI: 10.1112/plms.12227
|View full text |Cite
|
Sign up to set email alerts
|

Connected sums and involutive knot Floer homology

Abstract: We prove a formula for the conjugation action on the knot Floer complex of the connected sum of two knots. Using the formula we construct a homomorphism from the smooth concordance group to an abelian group consisting of chain complexes with homotopy automorphisms, modulo an equivalence relation. Using our connected sum formula, we perform some example computations of Hendricks and Manolescu's involutive invariants on large surgeries of connected sums of knots.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 30 publications
0
74
0
Order By: Relevance
“…Furthermore, using the grading change formula, the author computes the maps for closed surfaces with simple dividing sets when b 1 = 0 and b + 2 = 0 [31, Theorem 1.7]. The link cobordism maps also satisfy a version of conjugation invariance [30,Theorem 1.3] similar to the version satisfied by the standard 4-manifold invariants [23,Theorem 3.6]. Using this, and some further properties of the link cobordism maps, the author explores the relation between the cobordism maps and the Künneth theorem for connected sums, and in particular proves a connected sum formula for involutive knot Floer homology [30, Theorem 1.1].…”
Section: Further Developmentsmentioning
confidence: 99%
“…Furthermore, using the grading change formula, the author computes the maps for closed surfaces with simple dividing sets when b 1 = 0 and b + 2 = 0 [31, Theorem 1.7]. The link cobordism maps also satisfy a version of conjugation invariance [30,Theorem 1.3] similar to the version satisfied by the standard 4-manifold invariants [23,Theorem 3.6]. Using this, and some further properties of the link cobordism maps, the author explores the relation between the cobordism maps and the Künneth theorem for connected sums, and in particular proves a connected sum formula for involutive knot Floer homology [30, Theorem 1.1].…”
Section: Further Developmentsmentioning
confidence: 99%
“…In a recent paper , the second author showed that knot Floer homology gives an obstruction to ribbon concordance. In this short note, we prove an analogous result for Khovanov homology .…”
Section: Applicationsmentioning
confidence: 99%
“…By the functoriality of Khovanov homology, Khfalse(Dfalse)=Khfalse(trueC¯false)Khfalse(Cfalse). The second author showed in that D has the following nice topological description: There exist unknotted, unlinked 2‐spheres S1,Snfalse(R3L0false)×false[0,1false], and disjointly embedded 3‐dimensional 1‐handles h1,,hn in double-struckR3×I, where hi joins L0×false[0,1false] to Si and is disjoint from Sj for ji, such that D is obtained from false(L0×[0,1]false)S1Sn by embedded surgery along the handles h1,,hn. By Proposition , we have Khfalse(Dfalse)=±Khfalse(L0×[0,1]false)=±prefixidKh(L0).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They similarly considered the conjugation action on the knot Floer complex. Zemke [Zem17] showed that, under an appropriate equivalence relation, the set of knot Floer complexes together with the extra structure given by the conjugation action form a group, and that there is a homomorphism from the knot concordance group to this group. The aim of this note is to prove an involutive analog of [Hom17, Theorem 1].…”
Section: Introductionmentioning
confidence: 99%